Responsiveness of the B-ECOHIS to detect changes in OHRQoL following dental treatment of children with autism spectrum disorder - Viviane Andrade Cancio de PAULA; Khawana FAKER; Cristiane Baccin BENDO; Mônica Almeida TOSTES (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The Brazilian Early Childhood Oral Health Impact Scale (B-ECOHIS) is an oral health-related quality of life (OHRQoL) questionnaire. This paper aims to investigate the responsiveness of the B-ECOHIS to dental treatment in individuals diagnosed with autism spectrum disorder (ASD) and determine if dental treatment has an impact on OHRQoL. The survey targeted 27 ASD individuals aged 4 to 14 years attending the Acolher Project of the University Federal Fluminense. This project provides children and adolescents with disabilities with oral health services. A group of randomly selected caregivers self-completed the B-ECOHIS before and 14 days after their children's dental treatment. The dental treatment included meticulous screening, preventive treatment, and restorative treatment. Responsiveness was assessed by investigating the effect size (ES) and standardized response mean (SRM). Wilcoxon test was used to evaluate internal responsiveness (distribution-based approach). The B-ECOHIS showed significant changes in the total score (p<0.001) and in all domains. The ES of the total B-ECOHIS after treatment was 1.28 and ranged between 0.70 and 1.14 for the domains. The SRM for each of the domains was large, except for the symptom domain. The B-ECOHIS is sensitive and responsive to ASD individuals undergoing dental treatment. Individuals with ASD showed improvement in their OHRQoL score after dental treatment.